Karakteristik Krim Body Scrub Pada Variasi Perbandingan Bubuk Kulit Kopi Robusta dan Ekstrak Kulit Jeruk Nipis Serta Waktu Pengadukan - Tambak, Yosafat Anesta Tarigan; Putra, Gusti Putu Ganda; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
Body scrub cream is one of the cream dosage forms. Raw materials and stirring time in the cream making process affect its characteristics. The purpose of this study was to understand the effect of the ratio of robusta coffee skin powder and lime peel extract and stirring time in making body scrub cream and determine the best treatment in producing body scrub cream. The implemented design is Factorial Randomized Block Design (RBD), first factor of the comparison between robusta coffee skin powder: lime peel extract 1: 2, 1: 1, and 2: The second factor is stirring time of 15, 20, and 25 minutes. The variables observed were moisture content, pH, viscosity, spreadability, separation ratio, antioxidant activity, and organolopetic assessment. The results showed that the material ratio treatment had a very significant effect on water content, viscosity, spreadability, antioxidant activity, aroma, color, and texture. Stirring time treatment had a very significant effect on viscosity, spreadability, and antioxidant activity of body scrub cream. The interaction between treatments had a very significant effect on antioxidant activity. The treatment of the ratio of ingredients, stirring time, interaction between treatments had no effect on pH. The conclusion in this study is the treatment of the ratio of robusta coffee skin and lime peel extract 1: 2 and stirring time of 15 minutes is the best treatment in making body scrub cream, with characteristics of water content value 38.03%, pH 5, viscosity 30,000 cp, spreadability 5.49 cm, separation ratio =1, antioxidant activity (IC50) 243,688.65 ± 309.50 mg/L, aroma 5.30 (somewhat like - like), color 4.05 (normal - somewhat dislike), and texture 4.90 (normal - somewhat like).